2008
DOI: 10.1002/aic.11601
|View full text |Cite
|
Sign up to set email alerts
|

Reaction rate constant of CO2 hydrate formation and verification of old premises pertaining to hydrate growth kinetics

Abstract: in Wiley InterScience (www.interscience.wiley.com).Experimental data on the rate of carbon dioxide hydrate formation in a semibatch stirred-tank reactor was obtained using a particle-size analyzer capable of detecting particles as small as 0.6 nanometers in a closed-loop system. Experiments were carried out at temperatures between 275.3 and 279.4 K and pressures ranging from 2,014 to 3,047 kPa. The reaction rate constant of CO 2 hydrate formation was determined using a newly developed kinetic model independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
2
35
1
Order By: Relevance
“…[45] Studies of other crystal systems indicate that nucleation is likely to occur heterogeneously and generate particles larger than those predicted by homogeneous nucleation theory. [17] Modelling [22,47] Within this study, particles were found to have sizes ranging from 100 nm to 6 mm with a high variability in the particle sizes recorded.…”
Section: Particle Size Distributionmentioning
confidence: 83%
See 2 more Smart Citations
“…[45] Studies of other crystal systems indicate that nucleation is likely to occur heterogeneously and generate particles larger than those predicted by homogeneous nucleation theory. [17] Modelling [22,47] Within this study, particles were found to have sizes ranging from 100 nm to 6 mm with a high variability in the particle sizes recorded.…”
Section: Particle Size Distributionmentioning
confidence: 83%
“…Both gas consumption and temperature are notably different from previous experiments with pure clathrates. [17] With the semi-clathrate system, initial hydrate formation results in a temperature increase of nearly 1 K over a period of 400 s, after which the temperature plateaus. This would indicate that the system is using gas dissolved prior to turbidity in the liquid to feed hydrate growth rather than requiring gas transferred after turbidity from the vapour phase.…”
Section: Gas Consumption and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…A larger scale of a new apparatus which could operate with different gas-water contact modes was set up in order to test the hydrate-based separation processes for pre and post combustion capture of CO 2 . Bergeron and Servio (2008) obtained experimental data on the rate of carbon dioxide hydrate formation and then determined the reaction rate constant of CO 2 hydrate formation using a kinetic model independent of the dissolution rate at the vapourliquid water interface. In another study Bergeron and Servio (2009) measured the mole fraction of carbon dioxide in the bulk liquid phase and found that the mole fraction of carbon dioxide in the bulk liquid phase was constant during the growth period.…”
Section: Kinetic Study Of Co 2 Hydratesmentioning
confidence: 99%
“…The mechanism of CO 2 hydrate formation has been the subject of many experimental (Bergeron and Servio, 2008;Chun and Lee, 1996;Fleyfel and Devlin, 1991;Horvat et al, 2012;Malegaonkar et al, 1997;North et al, 1998), computational modeling (Englezos et al, 1987Lund et al, 1994;Shindo et al, 1993) and molecular dynamic (MD) simulation studies (Christiansen and Sloan, 1994;Shindo et al, 1995). Considerable practical research has been focused on the formation of gas hydrates from CO 2 -N 2 and CO 2 -H 2 gas mixtures Kumar et al, 2006;Linga et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%